Effect of Cryopreserved Cord Blood Serum Administration on Structural Changes of Joints During Induced Gonarthrosis in Rats - Vvedenskiy, Boris P.; Kovalev, Gennadiy A.; Dedukh, Ninel V.; Sandomirskiy, Boris P. (Problems of Cryobiology and Cryomedicine, 2016)
In the paper we assessed the morphological changes of rat’s knee joint tissues in arthrosis simulatiion and therapy with cryopreserved human cord blood serum. Gonarthrosis was simulated by a single injection into a joint cavity of 35Â° ethanol solution cooled down to â€“25Â°C. It has been found that in the control animals (untreated) at all the stages of monitoring the signs of gonarthrosis progressed. To day 7 in joint cavity there were found the tissue fragments containing detritus, and starting from day 14 the pannus formation was revealed. Intramuscular injection of either Alflutop drug (control group) or the cryopreserved human cord blood serum (experimental group) was accompanied by a positive dynamics of reparation, which was more pronounced when treating with cryopreserved human cord blood serum, but a complete restoration of an articular cartilage was not observed. Treatment with cryopreserved human cord blood serum was helpful in slowing down the degeneration of articular coating, preventing the pannus formation, it reduced the pathology activity in a joint capsule. More dense packing of erythrocytes in a cartilage was accompanied by restoration of their functional activity. Probl Cryobiol Cryomed 2016; 26(4): 361â€“374